Pavement Materials characterization of hot-mix asphalt mixes in Western Australia - Nega, Ainalem; Nikraz, Hamid; Leek, Colin; Ghadimi, Behzad (Trans Tech Publications Inc, 2013)
The use of deep strength asphalt materials characterization to construct and restore the heavily urban roads where damage has been induced is rapidly grown in Western Australia. Five different types of asphalt mixes were produced in laboratory to modify pavement performance mixture. The main role of this research is to evaluate the pavement materials characterization for Western Australia road. In this study, laboratory test for tensile strength, resilient modulus, wheel tracking, binder contents, Marshall Compaction, and air voids contents test were taken to analyze each asphalt mixtures. The results indicated that AC20-75 and AC14-75 asphalt mixes blow were in a good pavement performance as compared to other asphalt mixes. For a mix design purposed, all the asphalt mixes that are used in this study can strength and stable the stiffness of pavement that is notable, and the modification effect rank can be described as AC20-75 Blow > AC14-75 Blow > AC14-50 Blow > AC7-50 Blow > SMA7-50 Blow in this research.